2006
DOI: 10.1007/s11881-006-0004-4
|View full text |Cite
|
Sign up to set email alerts
|

Testing the double-deficit hypothesis in an adult sample

Abstract: The double-deficit hypothesis of dyslexia posits that reading deficits are more severe in individuals with weaknesses in phonological awareness and rapid naming than in individuals with deficits in only one of these reading composite skills. In this study, the hypothesis was tested in an adult sample as a model of reading achievement. Participants were parents of children referred for evaluation of reading difficulties. Approximately half of all participants reported difficulty learning to read in childhood an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
0
15
1
Order By: Relevance
“…In comparison to the three extant studies in which adult participants were used and DDH subtype comparisons were made (Cirino et al, 2005;Miller et al, 2006;Vukovic et al, 2004), the current results are only partially consistent. Vukovic et al (2004) examined the DDH with college students diagnosed with reading disabilities and descriptively compared the NS-D subtype (n=11), PA-D subtype (n=4), and DD subtype (n=5) on word reading and reading comprehension measures.…”
Section: Ddh Subtypes and Level Of Reading Impairmentcontrasting
confidence: 53%
See 1 more Smart Citation
“…In comparison to the three extant studies in which adult participants were used and DDH subtype comparisons were made (Cirino et al, 2005;Miller et al, 2006;Vukovic et al, 2004), the current results are only partially consistent. Vukovic et al (2004) examined the DDH with college students diagnosed with reading disabilities and descriptively compared the NS-D subtype (n=11), PA-D subtype (n=4), and DD subtype (n=5) on word reading and reading comprehension measures.…”
Section: Ddh Subtypes and Level Of Reading Impairmentcontrasting
confidence: 53%
“…These researchers did, however, find that the DD subtype was most impaired on pseudoword decoding accuracy and efficiency tasks in their sample of college students referred for learning problems. Miller et al (2006) investigated the DDH in a sample of parents of children with dyslexia, although it was not reported that the parents themselves had been diagnosed with dyslexia. Participants from the two single-deficit groups appear to have been aggregated into one group and then compared to the DD group, limiting comparison to the current study.…”
Section: Ddh Subtypes and Level Of Reading Impairmentmentioning
confidence: 99%
“…They emphasise the importance of assessing adults' reading fluency, because it reveals persistent deficits. A reading comprehension study showed that phonological awareness accounted for less of the variance in reading comprehension accuracy (Miller et al 2006) than did listening comprehension, working memory, IQ, vocabulary or general knowledge, all of which were found to be more crucial. In this study, no single cognitive process was dominant in predicting reading comprehension; instead, a combination of several processes seemed to provide the best account of reading comprehension difficulties.…”
Section: Dyslexia and Problems With Readingmentioning
confidence: 98%
“…This and other challenges in phonological ability seem to be the core deficit in dyslexia (Elbro 2004;Goswami 2002;Høien and Lundberg 1999;Samuelsson, Herkner and Lundberg 2003;Vellutino et al 2004). Miller et al (2006) tested the double-deficit hypothesis of dyslexia on adults (N 0133). The hypothesis posits that dyslexia is more severe in adults who have problems with both rapid naming and phonological awareness than in those who have only one of these major problems.…”
Section: Dyslexia and Problems With Readingmentioning
confidence: 99%
See 1 more Smart Citation